ЖОҒАРЫ ЖӘНЕ ЖОҒАРЫ ОҚУДАН КЕЙІНГІ БІЛІМ БЕРУ ПРОБЛЕМАЛАРЫ - Касенуалиева, З Е (Journal of Economic Research & Business Administration, 2015)
This article examines the current state and problems of development of higher and postgraduate education Republic of Kazakhstan.